Midwifery curriculum evaluation: Is the balance between theory and practice achieved? - Josi Noviani; Cindy Maharani Putri; Annisa Karima Harda; Ari Indra Susanti (Curricula: Journal of Curriculum Development, 2025)
Achieving a balance between theoretical knowledge and clinical practice remains a significant challenge in midwifery education. This literature review, conducted systematically using the PICO framework, aims to evaluate midwifery curricula that integrate theory and practice to better prepare students for the demands of the professional world. Five peer-reviewed studies published between 2020 and 2025 from various countries were analysed. The findings reveal recurring barriers in clinical learning, such as inadequate supervision, limited hands-on experience, and a misalignment between academic curricula and field-based practical requirements. Innovative strategies, including Simulation-Based Education (SBE), Competency-Based Education (CBE), Dedicated Education Units (DEU), and Student-Centred Learning (SCL), have demonstrated potential in improving students’ confidence and competence. However, the effectiveness of these approaches is contingent upon sufficient infrastructure and teaching resources. This review emphasizes the importance of continuous curriculum evaluation and educational innovation in strengthening the integration of theory and practice, ultimately enhancing the clinical readiness of midwifery graduates.   Abstrak Mencapai keseimbangan antara pengetahuan teoretis dan praktik klinis tetap menjadi tantangan besar dalam pendidikan kebidanan. Tinjauan pustaka ini dilakukan secara sistematis dengan menggunakan kerangka PICO, bertujuan untuk mengevaluasi kurikulum kebidanan yang mengintegrasikan teori dan praktik guna mempersiapkan mahasiswa menghadapi tuntutan dunia profesional. Lima studi yang telah melalui proses telaah sejawat dan diterbitkan antara tahun 2020 hingga 2025 dari berbagai negara dianalisis dalam kajian ini. Temuan menunjukkan adanya hambatan yang berulang dalam pembelajaran klinis, seperti supervisi yang tidak memadai, keterbatasan pengalaman langsung, serta ketidaksesuaian antara kurikulum akademik dan kebutuhan praktik di lapangan. Strategi inovatif seperti Simulation-Based Education (SBE), Competency-Based Education (CBE), Dedicated Education Units (DEU), dan Student-Centred Learning (SCL) menunjukkan potensi dalam meningkatkan kepercayaan diri dan kompetensi mahasiswa. Namun, efektivitas pendekatan-pendekatan ini sangat bergantung pada ketersediaan infrastruktur dan sumber daya pengajaran yang memadai. Tinjauan ini menekankan pentingnya evaluasi kurikulum secara berkelanjutan dan inovasi pendidikan untuk memperkuat integrasi antara teori dan praktik, sehingga pada akhirnya dapat meningkatkan kesiapan klinis lulusan kebidanan. Kata Kunci: evaluasi Kurikulum; kesenjangan teori dan praktik; pembelajaran berbasis simulasi; pendidikan berbasis kompetensi; pendidikan kebidanan